Preventive aspects of sexual transmission of sexually transmitted diseases acquired immune dPreventive aspects of sexual transmission of sexually transmitted diseases acquired immune deficiency syndrome in a high risk populationeficiency syndrome in a high risk population - Buddhakorala, K (My University, 1996)
A cross sectional comparative study was carried out during July 1994 to Aug 1995 between a population with high risk sexual behaviour in the tourist trade at Hikkaduwa and a matched working group. The objectives of the study were to compare the knowledge on STD/AIDS, to measure some priority prevention indicators, to measure 4 predictor variables in the sexual risk reduction behavior model, and to assess attitudes towards condom use. Nearly 100 per cent in both groups had of AIDS but more detailed knowledge was better among the SG. The knowledge on the use of a condom both for prevention of pregnancy and AIDS was significantly higher in the study group. The sexual activity based on number of persons having ever had one or more sexual encounters and the number of sexual acts with the most recent casual sexual partner was more among the control group than the study group. But the number of casual sexual partners during previous 12 months was higher in the SG